Psychometric Properties of the Georgian Version of Motivated Strategies for Learning Questionnaire (MSLQ) - Revishvili, Mariam; Tsereteli, Mzia; Aptarashvili, Ia (Georgian Psychological Journal, 2022)
The article concerns the psychometric properties of the Georgian version of the Motivated Strategies for Learning Questionnaire (MSLQ) such as factorial properties, internal consistency of the sub-scales and gender differences by factors of the motivation and learning strategies scales. 560 Bachelor program students from 17 higher education institutions participated in the study. The instrument assessing motivation and self–regulated learning combine two main scales: 1) motivational orientation scale, and 2) learning strategies scale. There are 81-items in the instrument measured on a 7-point Likert type scale where point 1 means ‘Does not at all correspond’ and point 7 ‘Fully corresponds’. The administration of the questionnaire requires about 20-30 minutes. Study results show that the Georgian version of the Motivated Strategies for Learning Questionnaire is similar by factorial properties to the original version of the instrument. Internal consistency value is .70 for the motivation scale and .80 for learning strategies scale which meets the instrument validation standard. Reliability values for the factors in the scales ​​range from .51 to .89. As for gender differences, male and female respondents showed statistically significant difference on both motivation factors (task value, control beliefs and self-efficacy for learning) and learning strategies factors (elaboration, organization, metacognitive self-regulation, time and study environment management and effort regulation). The above findings lead to the conclusion that the Georgian version of Motivated Strategies for Learning Questionnaire can be used for future research purposes.